2019
DOI: 10.1021/acsami.8b19072
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Factors Affecting the Electrochemical Performance of MoS2–Carbon Composite Catalysts for Hydrogen Evolution Reaction: Surface Defect and Electrical Resistance of Carbon Supports

Abstract: In MoS2–carbon composite catalysts for hydrogen evolution reaction (HER), the carbon materials generally act as supports to enhance the catalytic activity of MoS2 nanosheets. The carbon support provides a large surface area for increasing the MoS2 edge site density, and its physical structure can affect the electron transport rate in the composite catalysts. However, despite the importance of the carbon materials, direct observation of the effects of the physical properties of the carbon supports on the HER ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
(71 reference statements)
1
11
0
Order By: Relevance
“…Nevertheless, it is expected that the pore size of the carbon shells might be reduced due to their enhanced crystallinity after increasing the annealing temperature [31,32,33,34,35,36,37]. In addition, when the samples are heated at H 2 -mixed N 2 gas atmosphere, the thickness of the carbon shells can decrease since H 2 gas etches the activated carbon sites and decreases the growth rate of carbon layers during the formation of the graphitic carbon layer [38,39]. Accordingly, for PtFe 700_Ar and PtFe 900_Ar samples, thicker carbon shell layers might be obtained compared to those of PtFe 700_H 2 and PtFe 900_H 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is expected that the pore size of the carbon shells might be reduced due to their enhanced crystallinity after increasing the annealing temperature [31,32,33,34,35,36,37]. In addition, when the samples are heated at H 2 -mixed N 2 gas atmosphere, the thickness of the carbon shells can decrease since H 2 gas etches the activated carbon sites and decreases the growth rate of carbon layers during the formation of the graphitic carbon layer [38,39]. Accordingly, for PtFe 700_Ar and PtFe 900_Ar samples, thicker carbon shell layers might be obtained compared to those of PtFe 700_H 2 and PtFe 900_H 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The change in the carbon shell structure according to the annealing conditions can be understood to be for the following reasons. During the course of carbon shell formation, the strong interaction between H 2 molecules and carbon disrupts the C−C bond formation on the metal nanoparticles and carbon layers is etched under H 2 atmosphere, creating more defects and large pores [38,39]. In contrast, inert Ar gas does not affect the defect formation and carbon etching during the heat treatment, meaning dense and thick carbon shells can be formed [31,32,33,34,35,36,37].…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 ] For impurities, the insertion of carbon/nitrogen atoms will cause an increase in the density of states near the Fermi level. Therefore, the lattice customization strategy provides enhanced conduction paths for carriers, effectively activating redox reactions and promoting electron transfer [32a,33] . For lattice defects, more vacancies are produced due to the missing atom from its original lattice site, which is beneficial to capture electrons and improve catalyst activity.…”
Section: Types Of Nanomaterial‐based Electrochemical Sensorsmentioning
confidence: 99%
“…Carbon-based materials are widely used as HER catalyst because of their adjustable molecular structures, abundance, and strong tolerance to acidic/alkaline environments. Although carbon-based materials are inert to HER, the active site of the system can be modulated by doping atoms and tuning surface curvatures. Theoretical and experimental studies have shown that carbon-based materials with nonmetal atom doping can change the local charge or spin density of carbon atoms and improve the catalytic performance of carbon atoms. In nonmetal atoms, nitrogen (N) atom doping is used because the triple-coordination characteristic of nitrogen atoms can well match with the sp 2 -hybridized carbon bonding structure, and the geometrical structure of the sp 2 -carbon networks will not change when nitrogen atoms are doped. …”
Section: Introductionmentioning
confidence: 99%